Ritual Rajasuya Penanda Kuasa Era India Kuno - Duana Sutika, I Nyoman (Humanis, 2023)
This research reveals social realities in narrative literary works about the ruler's desire to achieve power, glory and glory. Rituals rajasuya in a piece of text sabhaparwa this is interesting to highlight because it is always preceded by war between rulers and is an archaic cultural tradition of the Ancient Indian era. This ritual is carried out more to legitimize power. The theory used is reception theory to discover, interpret and concretize what is expressed and implied. Data processing was carried out using the descriptive analysis method, namely describing the results obtained assisted by the hermeneutic method to understand the text. Search results show that the text sabhaparwa this is still appreciated by the Balinese people by carrying out intensive copying with the aim of making these texts known, read and interpreted by readers. Text parva including sabhaparwa This is adapted prose and shows its dependence on quotations from original works in Sanskrit